البيئة ومقومات حمايتها في الجزائر - شاهد, إلياس; دفرور, عبد النعيم (University of Eloued جامعة الوادي, 2016)
أدت الزيادات السكانية عبر العالم إلى تضاعف النشاط الصناعي والتجاري والاستهلاكي وزيادة في استهلاك الطاقة واستعمال الموارد الطبيعية، مما أدى إلى إلحاق أضرار كبيرة بالبيئة الطبيعية وأصبح يهدد العيش فيها بأمان، وهو ماجعل المهتمين بها يفكرون في السبل المثلى لحمايتها من التلوث، وعالجت هذه الدراسة مقومات حماية البيئة في الجزائر، حيث أسندت هذه المهمة إلى الهيئات الحكومية، وسنت العديد من التشريعات والقوانين في مجال حماية البيئة، وأوصت بضرورة النظر إلى حماية البيئة بمنظور تحقيق التنمية الاقتصادية والاجتماعية، وتشجيع سياسات الاقتصاد الأخضر والتنمية المستدامة، وتفعيل قوانين التربية البيئية، وتشجيع مساهمة الجمهور في حماية البيئة Population increase across the world lead to a doubling of the industrial, commercial and consumer activity and an increase in energy consumption as well as the use of natural resources resulting in significant damage to the natural environment and threatens to live safely. In response to that, many specialists start thinking about the best ways in order to protect it from pollution, This study addresses the elements of environmental protection in Algeria, assigning this mission to the government agencies, and to enact a number of laws and regulations in the field of environmental protection. It recommended that consideration have to be given to the protection of the environment perspective to achieve economic and social development, and the promotion of green economy policies, sustainable development and environmental education.
the environment and its elements of protection in Algeria
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: البيئة، التلوث،حماية البيئة، الجباية البيئة; environment, pollution, environmental protection, environmental tax